2002
DOI: 10.1073/pnas.052710099
|View full text |Cite
|
Sign up to set email alerts
|

The gas phase reaction of singlet dioxygen with water: A water-catalyzed mechanism

Abstract: Abs efficiently catalyze the conversion of molecular singlet oxygen ( 1 O2) plus water to hydrogen peroxide (HOOH), we used quantum chemical methods (B3LYP density functional theory) to delineate the most plausible mechanisms for the observed efficient conversion of water to HOOH. We find two reasonable pathways. In Pathway I, (i) H2O catalyzes the reaction of 1 O2 with a second water to form HOOOH; (ii) two HOOOH form a dimer, which rearranges to form the HOO-HOOO ؉ H2O complex; (iii) HOO-HOOO rearranges to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 42 publications
(29 reference statements)
6
91
0
2
Order By: Relevance
“…The HO and HO 2 formed here can go through reaction 9, leading to the formation of H 2 O ϩ 3 O 2 . We also find that H 2 O can catalyze the decomposition of HOOOH to 1 O 2 (4,22). Thus (30) and in the pulse radiolysis of air-saturated perchloric acid solution (23).…”
Section: [5]mentioning
confidence: 57%
See 1 more Smart Citation
“…The HO and HO 2 formed here can go through reaction 9, leading to the formation of H 2 O ϩ 3 O 2 . We also find that H 2 O can catalyze the decomposition of HOOOH to 1 O 2 (4,22). Thus (30) and in the pulse radiolysis of air-saturated perchloric acid solution (23).…”
Section: [5]mentioning
confidence: 57%
“…By means of 17 O NMR spectroscopy, Plesnicar and coworkers (32) concluded that the low-temperature ozonation of isopropyl alcohol and isopropyl methyl ether yields hydrogen trioxide H 2 O 3 (in addition to the hydrotrioxides of these compounds). Recently the antibody-catalyzed oxidation of water to hydrogen peroxide by 1 O 2 has been proposed to proceed through H 2 O 3 as the critical intermediate (3)(4)(5). This situation has changed with the recent synthesis of H 2 O 3 in argon matrices by the photolysis of the ozone-hydrogen peroxide complex (2), and we have now clarified the mechanism by using first-principles quantum mechanics.…”
Section: [5]mentioning
confidence: 99%
“…Su et al (2002) [229] calculated the cis form to be 10.0 kJ mol −1 higher a barrier-to-isomerization of 21.8 kJ mol −1 . We note that the first quantum chemical calculations (MP2) of the rotational potential of this molecule were done by Cremer (1978) [228] and predicted the cis form to be about 15.9 kJ mol −1 less stable and that there was a very high barrier-toisomerization of 46.4 kJ mol −1 .…”
Section: Sumamentioning
confidence: 99%
“…Reactions 6 and 7 (taking into account the principle of detailed balance for the various pathways) regenerate hydrogen and oxygen [88]. 12 Ozone does not interact with molecular hydrogen.…”
Section: Methodsmentioning
confidence: 99%